Transfusion Policy After Severe Postpartum Hemorrhage. Issue 3 (September 2015) - Prick, B.W.; Jansen, A.J.; Steegers, E.A.; Hop, W.C.; Essink-Bot, M.L.; Uyl-de Groot, C.A.; Akerboom, B.M.; van Alphen, M.; Bloemenkamp, K.W.; Boers, K.E.; Bremer, H.A.; Kwee, A.; et al.
<x xml:space="preserve">Abstract</x> (BJOG. 2014;121(8):1005–1014)